Kinetics of porphyrin adsorption and DNA-assisted desorption at the silica-water interface. - Zhang, M; Powell, H; Mackenzie, S; Unwin, P (2010)
Evanescent wave cavity ring-down spectroscopy (EW-CRDS) has been used to study in situ the kinetics of the adsorption of 5,10,15,20-tetrakis(4-N-methylpyridiniumyl)porphyrin (TMPyP) from pH 7.4 phosphate buffer solution (PBS) to the silica-water interface and the interaction of calf thymus DNA (CT-DNA) with the resulting TMPyP-functionalized surface. TMPyP was delivered to the silica surface using an impinging jet technique to allow relatively fast surface kinetics to be accessed. Adsorption was first-order in TMPyP, and the initial adsorption rate constant at the bare surface was found to be k = (4.1 +/- 0.6) x 10(-2) cm s(-1). A deceleration in the adsorption kinetics was observed at longer times that could be described semiquantitatively using an Elovich-type kinetic expression. The limiting value of the absorbance corresponded approximately to monolayer coverage (6.2 x 10(13) molecules cm(-2)). Exposure of the TMPyP-modified silica surface to CT-DNA, achieved by flowing CT-DNA solution over the functionalized surface, resulted in efficient desorption of the TMPyP. The desorption process was driven by the interaction of TMPyP with CT-DNA, which UV-vis spectroscopy indicated involved intercalative binding. The desorption kinetics were also simulated using complementary finite element modeling of convection-diffusion coupled to a surface process.